2011
DOI: 10.1007/s12094-011-0720-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy with bevacizumab (Avastin) for metastatic colorectal cancer

Abstract: During the last decade, the development of new drugs known as targeted therapies was the result of a better understanding of the processes involved in the transformation of normal cells into cancer. The term targeted therapy refers to drugs that selectively target specific molecular pathways involved in tumorigenesis or tumour progression. Angiogenesis is important for tumour growth and metastasis, and is an important target for new biological agents. Bevacizumab is a humanised recombinant antibody that preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…21,22 Therefore, identification of proangiogenic genes and their products that lead to angiogenesis is critical for providing new potential therapeutic targets. In current oncological practice, the VEGF-targeted agent bevacizumab has been established as a first-line treatment for metastatic CRC, [23][24][25] suggesting especially important roles for angiogenic factors in CRC progression. Here, we showed that GPR120 signaling promoted angiogenesis by inducing secretion of proangiogenic factors VEGF, IL-8 and COX-2-derived PGE 2 in vitro and in xenograph mouse model.…”
Section: Gpr120 Is Induced In Human Crc Tissues and Its Expression Ismentioning
confidence: 99%
“…21,22 Therefore, identification of proangiogenic genes and their products that lead to angiogenesis is critical for providing new potential therapeutic targets. In current oncological practice, the VEGF-targeted agent bevacizumab has been established as a first-line treatment for metastatic CRC, [23][24][25] suggesting especially important roles for angiogenic factors in CRC progression. Here, we showed that GPR120 signaling promoted angiogenesis by inducing secretion of proangiogenic factors VEGF, IL-8 and COX-2-derived PGE 2 in vitro and in xenograph mouse model.…”
Section: Gpr120 Is Induced In Human Crc Tissues and Its Expression Ismentioning
confidence: 99%
“…TSGF, a special substance discovered by Canadian scientists, is produced by malignant tumor cells (Koukourakis et al, 2011;Efferth, 2012;Duffy, 2013). As a new tumor marker, it can promote tumor formation and growth as well as proliferation of a large amount of peripheral capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Bevacizumab (Avastin), a humanized monoclonal antibody against VEGF, the most potent growth factor involved in tumour angiogenesis, was approved in the EU in 2005 for the treatment of carcinoma, non-small-cell lung cancer, colorectal cancer, carcinoma, renal cell cancer, and ovarian cancers [71][72][73][74] . Bevacizumab has been evaluated as first-line treatment in a phase II clinical trial with cisplatin and pemetrexed in patients with advanced mesothelioma.…”
Section: Tyrosine Kinase Inhibitors Against Vegfmentioning
confidence: 99%